Network of Affections: An Art-Educational Experience with Everyday Objects - Kumm, Rosely; Mendes, Samylla Oliveira (Revista do Colóquio, 2025)
In light of Jacques Le Goff’s reflections, this study seeks to understand how the constitution of memory, both individual and collective, can be related to common elements of daily life. It starts from the premise that these elements, even if devoid of monetary value, act as objects of memories and intimate experiences, thus acquiring symbolic value for their bearers. To highlight this issue, the research analyzes proposals by artists from Espírito Santo whose productions resignify everyday objects as devices of memory and identity. In parallel, an art-educational proposal was developed with postgraduate students, in which various objects were presented in order to awaken affective memories in the participants. These objects were connected by a string, forming a symbolic network of shared memories, which would highlight the collective dimension of experiences.